Efficient PIMRR Algorithm Based on Scheduling Measures for Improving Real Time Systems - Nageswara Rao, Siva; Jayaraman, Ramkumar; S.V.N Srinivasu, Dr (International Journal of Engineering and Technology, 2018)
Scheduling play an important role to perform a single (or) multiple process activities by considering scheduling criteriaâ€™s such as, waiting time, turnaround time, CPU utilization and context switches. The scheduling criteriaâ€™s mainly depends on the quantum time which is specific to real time systems. The challenges faced by the real time systems based on scheduling activities viz., higher waiting time, more context switches and high turnaround time. All the scheduling criteriaâ€™s are integrated to achieve Quality of Service (QoS) like throughput and delay. To improve the scheduling criteriaâ€™s like waiting time, context switches and turnaround time, PIMRR algorithm is proposed. The PIMRR algorithm is first integrated with modulo operation to provide priority to all the process. The average of all the processes burst time is equal to the quantum time. Performance analysis is done for PMIRR with the existing simple round robin, PRR, Priority based RR scheduling based on the scheduling criteriaâ€™s. Our results demonstrates that the PIMRR is more efficient compared to the existing ones, in terms of waiting time and turnaround time versus quantum time.Â Â Â